CURRENT STATUS OF LIAMBLIA INFECTION IN UZBEKISTAN (Modern education and development, 2025)
Relevance. According to the World Health Organization, approximately 200 million people worldwide are infected with giardiasis annually, of which 500 thousand (0.25%) develop clinical manifestations. In Russia, up to 150 thousand cases are registered annually, 80% of which occur in children under 14 years of age. In particular, this indicator is increasing significantly in Uzbekistan.